Historical wig styling : ancient egypt to the 1830s - Lowery, Allison (Focal Press costume topics series., 2019)
"Historical Wig Styling, Second Edition is a guide to creating beautiful, historically accurate hairstyles for theatrical productions and events. This volume covers hairstyles from Ancient Egypt through Romantic/Biedermeier styles of the 1820s and 30s. Chapters begin with an overview of historic figures and styles that influenced the look of each period, followed by step-by-step instructions and photographs showing the finished look from every angle. The book also explores the necessary supplies and styling products needed to create the perfect coif, tips for proper wig handling, a brief history of the makeup for each historical period, and basic styling techniques useful when working with wigs or real hair. New hairstyles featured in this edition include: - Ancient Egyptian male dreadlocks - Ancient Grecian male curls - Ancient Roman braided goddess - Braided Medieval lady - Regency hairstyle with a Classical influence With over a thousand full-color images and detailed instructions on how to create iconic hairstyles and makeup, Historical Wig Styling: Ancient Egypt to the 1830s is an excellent resource for professional costume designers and wig makers, as well as for students of Costume Design and Wig Making and Styling courses"- Resumé vydavatel